Can the absence of ants interfere in the arthropods abundance on corn plants (Zea mays L. - Poaceae)? - Gossler, Odair Santos; Lange, Denise; Fernandes, Wedson Desidério (Comunicata Scientiae, 2017)
Alternative methods to reduce the chemical control in monoculture have been widely assessed in order to diminish the pesticide use. Thus, the efficiency of predator arthropods who work as population controllers in many agro-ecosystems has been tested. The current study aim to verify if the presence of ants interfere in the amount of arthropod herbivores and predators on corn plants, Zea mays L. (Poaceae). A total of 100 plants were assessed, out of them, 50 were isolated from ants and the other 50 were not. There were 25 taxa of arthropods on corn plants, in which 14 were herbivorous and 11 predators. The ants’ free access to the plants negatively influenced the Diabrotica speciosa (Germar, 1824) (Coleoptera: Chrysomelidae) amount, which is an important herbivorous plague in corn monoculture. It was also observed the greater amount of Doru sp.1 (Dermaptera: Forficulidae) on plants containing ants. Considering the assessed plants, the presence of ants did not influenced the abundance of other arthropods. These results suggest that the ant-plant-herbivore interactions in corn monoculture is a complex system, and the presence of predatory ants in plants not always influence the presence of other arthropods.